Understanding terrorism in America : from the Klan to al Qaeda - Hewitt, Christopher (Routledge studies in extremism and democracy., 2003)
Essential reading for students of American politics and terrorism. It also provides a highly readable account for interested readers wishing to know more about a topic which has recently become tragically relevant in world affairs.